Intratumoral HLA-DR−/CD33+/CD11b+ Myeloid-Derived Suppressor Cells Predict Response to Neoadjuvant Chemoradiotherapy in Locally Advanced Rectal Cancer - Hasnis, Erez; Dahan, Aviva; Khoury, Wissam; Duek, Daniel; Fisher, Yael; Beny, Alex; Shaked, Yuval; Chowers, Yehuda; Half, Elizabeth E. (Frontiers in Oncology, 2020)
Capecitabine-based neoadjuvant chemoradiation therapy (nCRT) is currently the mainstay of treatment for locally advanced rectal cancer (LARC), prior to surgical tumor removal. While response to this treatment is partial, it carries significant risk of side effects. As of today, there is no accepted model to predict tumor response, and allow for patient stratification. The level of circulating Myeloid-derived suppressor cells (MDSCs), a subpopulation of early myeloid cells (EMCs), has been shown to correlate with prognosis and response to therapy in advanced colon cancer, but their role in LARC is not clear. We sought to study the effect of intratumoral and circulating levels of different EMCs subpopulations including MDSCs on response to nCRT. We analyzed tumor, normal mucosa, and peripheral blood samples from 25 LARC patients for their different EMCs subpopulation before and after nCRT, and correlated them with degree of pathologic response, as determined postoperatively. In addition, we compared LARC patient to 10 healthy donors and 6 metastatic patients. CD33+HLA-DR-CD16-CD11b+EMCs in the circulation of LARC patients were found to inhibit T-cell activation. Furthermore, elevated levels of CD33+HLA-DR- myeloid cells were found in the tumor relative to normal mucosa, but not in the circulation when compared to healthy subjects. Moreover, intratumoral, but not circulating levels of MDSCs correlated with clinical stage and response to therapy in patients treated with nCRT, with high levels of MDSCs significantly predicting poor response to nCRT. Importantly, therapy by itself, had significant differential effects on MDSC levels, leading to increased circulating MDSCs, concomitantly with decreasing intratumoral MDSCs. Our results suggest that high levels of intratumoral, but not circulating MDSCs may confer drug resistance due to immunomodulatory effects, and serve as a biomarker for patient stratification and decision-making prior to nCRT.